Nanobiosensing based on optically selected antibodies and superparamagnetic labels for rapid and highly sensitive quantification of polyvalent hepatitis B surface antigen. Issue 21 (17th May 2021) - Bragina, Vera A.; Orlov, Alexey V.; Znoyko, Sergey L.; Pushkarev, Averyan V.; Novichikhin, Denis O.; Guteneva, Natalia V.; Nikitin, Maxim P.; Gorshkov, Boris G.; Nikitin, Petr I.
Abstract : Magnetic LF assay for rapid quantification of HBsAg in serum. Abstract : Hepatitis B surface antigen (HBsAg) is the most clinically relevant serological marker of hepatitis B virus (HBV) infection. Its detection in blood is extremely important for identification of asymptomatic individuals or chronic HBV carriers, screening blood donors, and early seroconversion. Rapid point-of-care HBsAg tests are predominantly qualitative, and their analytical sensitivity does not meet the requirements of regulatory agencies. We present a highly sensitive lateral flow assay based on superparamagnetic nanoparticles for rapid quantification (within 30 min) of polyvalent HBsAg in serum. The demonstrated limit of detection (LOD) of 80 pg mL −1 in human serum is better than both the FDA recommendations for HBsAg assays (which is 0.5 ng mL −1 ) and the sensitivity of traditional laboratory-based methods such as enzyme linked immunosorbent assays. Along with the attractive LOD at lower concentrations and the wide linear dynamic range of more than 2.5 orders, the assay features rapidity, user-friendliness, on-site operation and effective performance in the complex biological medium. These are due to the combination of the immunochromatographic approach with a highly sensitive electronic registration of superparamagnetic nanolabels over the entire volume of a 3D test structure by their non-linear magnetization and selection of optimal antibodies by original optical label-free methods. The developed cost-efficient bioanalytical technology can be used in many socially important fields such as out-of-lab screening and diagnosis of HBV infection at a point-of-demand, especially in hard-to-reach or sparsely populated areas, as well as highly endemic regions.